1964
DOI: 10.3181/00379727-115-28922
|View full text |Cite
|
Sign up to set email alerts
|

Phytic Acid Studies.

Abstract: Phytic acid has interested analytical chemists, biochemists, and nutritionists for several years. Brown et al( 1) recently supported Neuberg's proposed structure and concluded that of the 18 acid hydrogens in the Neuberg model, only 1 2 were available for titration in aqueous solution.Chicks fed purified diets containing sesame meal ( 2 ,3) or isolated soybean protein (4) as the sole source of protein developed zinc deficiency symptoms, although the diet contained more than the optimum level of zinc. *Arizona … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(29 citation statements)
references
References 1 publication
0
29
0
Order By: Relevance
“…Zn . cadmium, whereas Maddaiah et al (1964), using a different titration method, reported the stability order as Zn . Cu .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn . cadmium, whereas Maddaiah et al (1964), using a different titration method, reported the stability order as Zn . Cu .…”
Section: Discussionmentioning
confidence: 99%
“…The stability of InsP 6 -metal complexes has been estimated by in vitro titration (Maddaiah et al, 1964;Vohra et al, 1965;Persson et al, 1998). The binding strength of InsP 6 with metal is stronger for Zn and Cu than for Fe, Mn, and Ca.…”
mentioning
confidence: 99%
“…Notionally, the phytate molecule carries a maximum of twelve negative charges and could potentially chelate six Ca atoms although the affinity of phytate is greater for certain other divalent cations, including zinc and copper (Maddaiah et al, 1964;Vohra et al, 1965). Nevertheless, Ca 2+ is a dominant cation in diets and consequently de novo formation of insoluble Ca-phytate complexes in the gut at conducive pH levels assumes importance (Wise, 1983;Angel et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…This eliminates the need for external addition of phosphorous to the feed, which incurs costs and also contributes to environmental pollution [3,23,43]. Removal of phytate from the feed also has other advantages in terms of overcoming its negative nutritional eVects such as decrease in the bioavailability of vital minerals [20,21,27,30], impairing the function of digestive enzymes or decrease in the digestibility of feed protein [2,3,17]. For the phytase to be eVective, it needs to be thermostable enough to withstand the high temperatures used during feed preparation.…”
Section: Introductionmentioning
confidence: 99%